Quelques effets sur la pratique de la traduction d’un concept : le déconstructivisme graphique depuis les années 1980 - Yann Aucompte; Stéphane Darricau (Appareil)
This article deals with the problems that arise when a philosophical concept is translated and applied to the practice of design. Our field of study will be the current of “deconstructionist graphic design” which appeared and developed in the United States during the 1980s and 1990s. Indeed this moment of the history of graphic design raises numerous questions about the act of translating, from the literary standpoint of the concepts borrowed from “French Theory” to the translation —as defined by the sociology of translation—of this discourse into design processes and attitudes. Jacques Derrida’s déconstruction enjoyed a wide success in the 1980s, reaching numerous and diverse social spheres: universities, trade unions, culture, politics. This notion was espoused by a certain strand of the graphic design field, giving birth to singular formal tropes. Thus, analyzing how “déconstruction” was translated into a practical tool asks for a description of the ways it went through numerous and varied social, political and cultural fields. It is the necessary condition to understand the true political subtext and implications of “deconstructionist graphic design”.